Mxene enrich concentration solar power (CSP) coolant - Kadirgama, Kumaran; Chelian, Ilen; Rahman, Md Mustafizur; Devarajan, Ramasamy; Mahendran, Samykano; Samylingam, Lingenthiran; Rahman, Saidur (2021)
The increasing effect of massive climate change due to greenhouse gas emission Main cost in CSP plant is the heat transfer fluid and thermal energy storage system Currently, most of the molten salt HTF works below 600 ℃, by increasing the boiling point will increase the efficiency of CSP system Good thermophysical properties – this is necessary to have efficient heat transfer during the HTF flows in the solar field block/heat exchanger